أثر جودة حياة العمل في الالتزام التنظيمي دراسة ميدانية على مركز خدمة المواطن ( النافذة الواحدة ) محافظة دمشق - زاهر, تيسير (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تناقش هذه الدراسة مفهوم جودة حياة العمل والالتزام التنظيمي للعاملين من خلال عرض إطار نظري للمفهومين واهم الدراسات المستندة حول العلاقة بينهما بالإضافة إلى تعزيز الدراسة النظرية بدراسات ميدانية على مركز خدمة المواطن في محافظة دمشق .وهدفت الدراسة إلى معرفة مدى توفر أبعاد جودة حياة العمل في مركز خدمة المواطن لمحافظة دمشق و معرفة مستوى الالتزام التنظيمي والعلاقة بينهما . ومن أهم النتائج التي توصلت إليها الدراسة وجود علاقة إيجابية وذات دلالة إحصائية ما بين استخدام جودة حياة العمل والالتزام التنظيمي وتختلف حسب عناصر كل منهما بنسب متفاوته.This study discusses the concept of quality of work life and Organizational commitment to employees through the presentation of a theoretical framework of concepts and the most important based on the relationship between the two studies in addition to strengthening theoretical study field studies . On the citizen service center in the province of DamascusThe study aimed to find out the availability of the quality of work life in the dimensions of the citizen service center to the province of Damascus and knowledge of the regulatory level of commitment and the relationship between them.Among the most important findings of the study and a positive and statistically significant relationship with between the use of the quality of work life and organizational commitment and vary depending on the elements of each varying degrees.